Sound Horeg from the Perspective of Maṣlaḥah Mursalah: An Analysis ofthe East Java Indonesian Ulema Council (MUI) Fatwa No. 1 of 2025 - Rahman, Nico; Ulum, Bahrul (MAQASIDI: Jurnal Syariah dan Hukum published by the Islamic Criminal Law Program of the Sharia and Islamic Economics Department at the Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh, 2025)
The phenomenon of using sound horeg—a high-volume loudspeaker system with a dominant bass—has become a trend in various regions of Indonesia, particularly in entertainment events and public gatherings. While it provides entertainment value and cultural appeal, its usage often triggers noise pollution, public disturbances, and social conflicts. In response to this phenomenon, the Indonesian Ulema Council (MUI) of East Java issued Fatwa No. 1 of 2025, which provides ethical and religious guidelines regarding the use of sound horeg. This study employs a qualitative descriptive-analytical approach with a library research method, focusing on the content analysis of the fatwa through the perspective of maslahah mursalah. The aim is to examine the content of MUI East Java Fatwa No. 1 of 2025, analyze the maslahah mursalah considerations underlying its issuance, and assess its social and religious implications within society. The findings indicate that the fatwa explicitly declares the use of sound horeg as haram, since it generates more harm than benefit. Nevertheless, the fatwa provides certain exceptions, namely when the use of sound equipment is conducted in a reasonable manner, without excess, and without causing harm to the surrounding community.